Connections: Ideas for Writing - Hancock, Sheila and Hancock, Ed. (New York Harcourt Brace Jovanovich, Inc., 1974)
Through seeing the work of experienced writers, you should come to be able to write at a higher level. Different exercises will take you through a new way of thinking and writing.
Keywords: Writing